Cytokines as therapeutic agents and targets in heart disease. (October 2018) - Dubnika, Arita; Manoukian, Martin A.C.; Mohammadi, M. Rezaa; Parekh, Mansi Bharat; Gurjarpadhye, Abhijit Achyut; Inayathullah, Mohammed; Dubniks, Viktors; Lakey, Jonathan R.T.; Rajadas, Jayakumar
Graphical abstract: Highlights: Cytokine based therapies have a potential to reduce post-infarct heart failure and chronic ischemia. Combinations of therapeutic cytokines and substances that control cytokine levels could be more effective treatment therapy. Further clinical studies are necessary to determine correct targets, dosages, long-term efficiency and safety of cytokines. Individualized cytokine based therapies could be the next major advance in the treatment of cardiovascular diseases. Abstract: Cytokine therapies have emerged during the past decade as promising noninvasive treatments for heart disease. In general, current drug treatments are directed towards symptom control and prevention of disease progression; however, many agents also produce cause side effects that alter quality of life. Cytokine based therapies have the potential to reduce post-infarct heart failure and chronic ischemia by stimulating the proliferation and differentiation of endothelial cells and bone marrow hematopoietic stem cells and mobilizing these cells toward ischemic tissue. In turn, these mobilized cell populations contribute to myocardial regeneration. In contrast, over-expression of several cytokines has been linked to a variety of heart diseases; thus, therapies targeting and monitoring these cytokines are of great interest. Here we summarize results from clinical studies on cytokines as therapeutic agents or therapeutic targets in the treatment for heart disease as well as cytokines involved in the evolution of heart disease.